Facile Surface Laser Modification of Nickel Foams for Efficient Water Oxidation Electrocatalysis. Issue 11 (8th June 2021) - Li, Yejun; Cao, Youwei; Duan, Ran; Qi, Weihong; Zhang, Yangyang; Xie, Haipeng; Tong, Yonggang; Gao, Xiaohui; Yin, Kai; Zhang, Gufei; Wei, Haigen; He, Jun
Abstract: Despite the recent efforts and progress on the transition metal‐based electrocatalysts for water splitting, it is still a challenge to fabricate oxygen evolution reaction electrocatalysts with high performance, simultaneously via a simple, facile, and environment‐friendly way. Herein, we report a facile strategy for the fabrication of NiFe oxides‐based micro/nano‐structures on Ni foams via simple femtosecond laser ablation, where the Ni : Fe ratio can be readily tuned by changing the amount of Fe precursors dropped on the Ni foams. The resulted electrocatalysts exhibit excellent oxygen evolution reaction activity with low overpotentials of 221 and 241 mV at 25 and 50 mA cm −2, and good long‐term durability under high current density in alkaline condition, suggesting great potentials for practical applications. Abstract : Green synthesis : Via simple laser ablation on nickel foams (NFs), NiFe oxides micro/nano‐structures with varied Ni : Fe ratio are fabricated on the NF surface. The obtained NiFe oxides electrocatalysts have demonstrated excellent oxygen evolution reaction (OER) activity and good long‐term stability. The present method is facile, fast, sustainable, and environmentally friendly, which can be easily generalized to other metal systems with potential for practical applications.